2020
DOI: 10.3390/brainsci10060343
|View full text |Cite
|
Sign up to set email alerts
|

Dream Recall upon Awakening from Non-Rapid Eye Movement Sleep in Older Adults: Electrophysiological Pattern and Qualitative Features

Abstract: Several findings support the activation hypothesis, positing that cortical arousal promotes dream recall (DR). However, most studies have been carried out on young participants, while the electrophysiological (EEG) correlates of DR in older people are still mostly unknown. We aimed to test the activation hypothesis on 20 elders, focusing on the Non-Rapid Eye Movement (NREM) sleep stage. All the subjects underwent polysomnography, and a dream report was collected upon their awakening from NREM sleep. Nine subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 57 publications
(95 reference statements)
2
27
0
Order By: Relevance
“…26 In this vein, several studies revealed the relationship between higher cortical arousal during NREM sleep (increased fast-frequencies and/or reduced slow-frequencies) and DR both in healthy and clinical groups. 5,8,9,11,12 Besides, we confirmed that the parietal and occipital regions are involved in sleep mentation, as suggested by early studies. 27 Consistently, Eichenlaub and collaborators 18 revealed that high dream recall frequency was associated with increased activity in the temporo-parietal junction at rest.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…26 In this vein, several studies revealed the relationship between higher cortical arousal during NREM sleep (increased fast-frequencies and/or reduced slow-frequencies) and DR both in healthy and clinical groups. 5,8,9,11,12 Besides, we confirmed that the parietal and occipital regions are involved in sleep mentation, as suggested by early studies. 27 Consistently, Eichenlaub and collaborators 18 revealed that high dream recall frequency was associated with increased activity in the temporo-parietal junction at rest.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings on EEG correlates of DR during REM sleep overlap the EEG pattern observed during NREM sleep, 5,8,10,11 providing support to the one generator model of mental sleep activity. 26 In this vein, several studies revealed the relationship between higher cortical arousal during NREM sleep (increased fast-frequencies and/or reduced slow-frequencies) and DR both in healthy and clinical groups.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…It is also now clear that the complexity and story-like characteristics of dream reports are related to sleep stages but also, and even more so, to circadian rhythms leading to more vivid and complex dreams in the morning than in the early night [e.g., (13)(14)(15)]. Recent developments have provided strong experimental arguments in favor of the arousal-retrieval model (16), proposing that awakenings when dream content is still in short-term memory are necessary to encode dreams into longterm memory (17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%